Phytoarchitecture Design Requires a Plant Selection Framework to Combat Air Contaminants in Building Areas Sustainably - Harida Samudro; Ganjar Samudro; Sarwoko Mangkoedihardjo (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Empowerment of plants to maintain the indoor and outdoor air quality of a building area promises occupant health and sustainable use of the building. In supporting plants' functional role, this study proposes a novel approach for a general framework for selecting plants. The method to achieve the objectives of this study was based on previous empirical studies conducted in various places under different environmental quality conditions. The essential findings of the selected literature became part of the technical feasibility process in selecting plants. Significant results indicate the mechanism of controlling airborne contaminants by plants through aerial parts and growth media. Gaseous pollutants can be absorbed along with carbon dioxide absorption, while particulate matter is deposited on the leaf surface. Some other contaminants enter the plant growth medium, which plants can process with microbes in the root zone. The use of plants for indoor and outdoor phytoremediation is various plant species, sourced and selected from a retrospective study, locally available and standard plants, and popular plants. These findings were developed to include assessments of contaminant-plant interactions and plant-specific experiments. The implications of the plant selection framework can be one of the promising methods in designing sustainable building phytoarchitectures.